Transarterial chemoembolization combined donafenib with/without PD-1 for unresectable HCC in a multicenter retrospective study - Li, Hao; Wang, Jiacheng; Zhang, Guokun; Kuang, Donglin; Li, Yanliang; He, Xiang; Xing, Cheng; Wang, Yong; Shi, Ming; Han, Xinwei; Ren, Jianzhuang; Duan, Xuhua (Frontiers in Immunology, 2023)
Background & aims This multicenter retrospective study evaluated the efficacy and safety of transarterial chemoembolization (TACE) combined with donafenib and a programmed death-1 (PD-1) inhibitor (TACE+DP) and TACE combined with donafenib (TACE+D) for unresectable hepatocellular carcinoma (uHCC). Methods The clinical data of 388 patients with uHCC who received TACE+DP or TACE+D as first-line treatment at six Chinese academic centers from July 2021 to July 2022 were collected and analyzed retrospectively. Patients in the TACE+DP group received an intravenous administration of a PD-1 inhibitor every three weeks and oral donafenib (0.2 g) twice daily until intolerable toxicity or disease progression. Patients in the TACE+D group received the same dose of donafenib for 3–5 days after TACE. Overall survival (OS) and progression-free survival (PFS)were analyzed by Kaplan-Meier method and log-rank test. The tumor response was compared between the two groups according to modified RECIST criteria. Adverse events were also analyzed between the two groups Results The TACE+D group included 157 patients and the TACE+DP group included 166 patients. Patients in the TACE+DP group had a longer median OS (18.1 vs. 13.2 months, P<0.001) and longer median PFS (10.6 vs. 7.9 months, P<0.001) than those in the TACE+D group. Patients in the TACE+DP group achieved a greater objective response rate (ORR; 50.6% vs. 41.4%, P=0.019) and greater disease control rate (DCR) (89.2% vs. 82.8%, P=0.010) than those in the TACE+D group. No significant differences were found in the incidence or severity of adverse events between the TACE+DP and TACE+D groups (any grade: 92.9% vs. 94.6%, P=0.270; grade 3 or 4: 33.8% vs. 37.3%, P=0.253). Conclusion With favorable safety and tolerability, TACE combined with donafenib and PD-1 inhibitors significantly improved PFS, OS, and ORR compared to TACE combined with donafenib.